The KiVa antibullying curriculum and outcome: Does fidelity matter? - Anne Haataja; Marinus Voeten; Aaron J. Boulton; Annarilla Ahtola; Elisa Poskiparta; Christina Salmivalli (Elsevier Ltd, 2022)
Research on school-based prevention suggests that the success of prevention programs depends
on whether they are implemented as intended. In antibullying program evaluations, however,
limited attention has been paid to implementation fidelity. The present study fills in this gap by
examining the link between the implementation of the KiVa antibullying program and outcome.
With a large sample of 7413 students (7–12 years) from 417 classrooms within 76 elementary
schools, we tested whether the degree of implementation of the student lessons in the KiVa
curriculum was related to the effectiveness of the program in reducing bullying problems in
classrooms. Results of multilevel structural equation modeling revealed that after nine months
of implementation, lesson adherence as well as lesson preparation time (but not duration of
lessons) were associated with reductions in victimization at the classroom level. No statistically
significant effects, however, were found for classroom-level bullying. The different outcomes for
victimization and bullying as well as the importance of documenting program fidelity are
discussed.